Physical Properties of Wood in Poplar Clones ’I-214’ and ’S1-8’ - Iva Ištok (University of Zagreb, Faculty of Forestry and Wood Technology, 2016)
Physical properties play an important role in predicting the quality of wood raw material. Variation in wood density and wood shrinkage of two different poplar clones cultivated on plantation “Drnje” near Koprivnica in Croatia was measured. One of poplar clones is ’I-214’, whose wood properties have already been studied and often compared. Other poplar clone is ʻS1-8ʼ, whose wood properties have been poorly researched, despite its good survival and growth rate. The results indicate that wood density of clone ’I-214’ is significantly higher in comparison to clone ʻS1-8ʼ, but the difference, as far as practice is concerned, is negligible. In both clones, wood density increases and shrinkage decreases from pith to bark. Increased growth rate has a negative effect on wood density of researched clones.